Economic growth in the dynamic Asia-Pacific Region - Hopkinson, Nicholas (HMSO LondonGB, 1993)
Examines the economic growth in the region. Answers the question, why have the Asia-Pacific economies developed successfully? Focuses on the threats and challenges to continued growth; growing trade frictions with the EC and North America; and, the evolving Asia-Pacific Regional Trading Bloc.